Assessing and Measuring the Performance of Energy Efficiency Projects - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2017)
Energy efficiency is a cost-effective solution to meet energy, climate change, and sustainabledevelopment goals and critical for supporting access to affordable, reliable, and sustainableenergy services in developing countries. The energy efficiency potential is vast and largelyuntapped across the world. This is widely recognized by most governments, the developmentcommunity, and international organizations, and forms the foundation of global initiatives such asSustainable Energy for All. The benefits of improving energy efficiency are multiple, but so are the barriers. There is no silver bullet, but recognizing the multiple benefits of energy efficiency - including energy savings, as well as others and making them more visible and credible is an integral part of the solution. If demonstrated suitably, these multiple benefits can motivate stakeholders to invest and participate in energy efficiency programs. The report makes the case that M&V should be a critical aspect of any energy efficiency project or program in order to ensure value for money, justify continued or increased funding, as well as provide the basis of performance-based payment mechanisms. M&V is essential to assess resource savings and to ensure that savings persist over time. Energy efficiency practitioners use M&V for several reasons, such as, to: improve engineering design and project costing; enhance energy savings through adjustments in facility operations and maintenance; document financial transactions; enhance financing for energy efficiency projects; and support development of broader energy efficiency programs.